From Sophora japonica to Smart Nanomedicine: Molecular Docking Simulations and Multifaceted Applications of CaO Nanoparticles - Alpaslan, Ecem Baykal; Attar, Azade; Aktas, Emre; Yapaoz, Melda Altikatoglu (AMER CHEMICAL SOC, 2025)
The growing demand for multifunctional nanomaterials in biomedical and environmental applications has driven the need for sustainable synthesis methods and comprehensive performance evaluations. In this study, calcium oxide nanoparticles (CaONPs) were synthesized using Sophora japonica extract via a green route, comprehensively characterized, and evaluated for biomedical and environmental applications. UV-vis spectroscopy confirmed the formation of CaONPs with a characteristic absorption peak at 321 nm. SEM showed spherical morphology with an average size of 30-70 nm, and FT-IR analysis confirmed the removal of organic residues postcalcination. X-ray diffraction analysis revealed sharp peaks corresponding to crystalline CaO with an average crystallite size of 53.45 nm. Molecular docking simulations were performed to evaluate the binding potential of synthesized CaONPs against selected bacterial outer membrane proteins (7NG9, 1BY3, 1FEB, 2HDF, and 4C4V) and the FDPS enzyme. The results revealed that CaO exhibited strong and stable binding interactions, comparable to or exceeding those of reference drugs, suggesting its promise as a dual-function bioactive agent. The calcinated CaONPs exhibited notable antibacterial and antifungal activity, with inhibition zones up to 18 mm, which enhanced up to 27 mm in combination with antibiotics/antifungals. In drug delivery studies, Zoledronic acid-loaded CaONPs showed pH-responsive behavior, releasing 92% of the drug at 250 h at pH 5.0, suggesting targeted delivery potential in acidic tumor environments. CaONPs showed no toxicity to Saos-2 osteosarcoma cells with 82% cell viability at 500 mu g/mL and 78% cell viability at 1000 mu g/mL. Furthermore, CaONPs achieved 93% removal efficiency of Congo red at 50 degrees C and pH 5.0 in 24 h, highlighting their potential in wastewater treatment. Synthesized CaONPs exhibited antimicrobial, drug delivery, and dye degradation properties while maintaining biocompatibility. Their pH-dependent drug release performance and strong synergistic antimicrobial effects highlight their applicability in antibiotic resistance, cancer therapy, and wastewater treatment.
Keywords: OXIDE NANOPARTICLES; BIOSYNTHESIS; VALIDATION; IMMATURUS; DELIVERY; EXTRACT; WASTE; Chemistry